Analisis Kemampuan Matematika Siswa Dalam Memecahkan Masalah Teorema Phytagoras Di Mts Terpadu Al Firdaus - Muawanah, Sholihatul; Rahmawati, Arum Dwi; Mashuri, Anwas (Global Education Journal, 2023)
Education is providing training through a process of teaching, guidance and leadership from people who know more about an object. The result of education is a change in a person's attitudes and behavior towards a value attached to a person or group of people. Education that is able to support future development is education that is able to develop the potential of students. One field of study that has an important role in the world of education and facing everyday life problems is mathematics. One of the abilities that students need to develop at school is the ability to understand concepts which can then be used to solve mathematical problems. Mathematical problem solving abilities aim to form initial abilities to learn mathematics that can be used in the mathematics learning process in mathematics material at school. In this study, researchers used the Polya stage in the form of 4 steps to examine students in class VIII of MTs Terpadu Al Firdaus. The female students who were research subjects were classified as low ability because they had low scores. There was 1 subject who had problems with initial mathematical abilities, then 1 subject with a lack of motivation, and 2 other subjects had problems such as lack of concentration and accuracy. This research was conducted to determine the ability of female students in solving mathematical problems, especially in the subject of the Pythagorean theorem. Apart from that, this research can also be a suggestion for teachers or educators in guiding students who need special attention.